Eve / 1 - Carey, Anna (Eve, 2011)
In 2032, sixteen years after a deadly virus has wiped out most of the population, Eve discovers the terrible fate that awaits students when they graduate from their all-girls school, and she sets off on a treacherous journey into the wilds of the New America, searching for a place where she can survive.